(untitled) (Journal of Contemporary Studies, 2025)
This paper explores AI’s influence on military decision-making at the tactical, operational, and strategic levels. At the tactical level, AI enhances speed and precision, providing real-time data analysis and decision support in high-risk, time-sensitive situations. At the strategic level, where decisions carry broader geopolitical consequences, human oversight remains dominant due to the complexity and potential for inadvertent escalation. Humans and machines collaborate at the operational level, with machines having more autonomy at the tactical level and humans dominating at the strategic level. The paper concludes that military planners must carefully evaluate the appropriate balance of AI autonomy and human control across these levels. It also cautions against the risks of an emerging AI arms race and the dangers posed by asymmetric AI development, where uneven technological capabilities among nations could lead to instability and unpredictable escalation.